Molecular targeting of prodigiosin against anti-inflammatory genes cyclooxygenase-1 and -2. (March 2023) - Anitha, Jaganathan; Muthusankar, Aathi; Viswanathan, Sundram; Murugesan, Palanivel; Gayathri, Nallani Chakravarthula; Selvakumar, Rajendran; Premkumar, Thathan
Abstract: The prodigiosin produced by the bacteria Serratia marcescens (SM) has been isolated and optimized with the streak plate method from different natural sources, such as human urine (SM1), soil (SM2), vegetable matter ( Cucurbita maxima, SM3) and water (SM4) . The isolated prodigiosin was confirmed as SM by its morphological characteristics, genomic size (1.5 kb), identification, and protein purification (4 kDa) using SDS-PAGE. Further, the total cell protein was confirmed and purified through thin layer chromatography (TLC) and high performance liquid chromatography (HPLC). The prodigiosin exhibited good microbial activity against selected Gram-positive bacteria and fungi. The binding efficiency of prodigiosin against cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) genes was assessed using an in silico molecular docking method that suggested higher binding efficiency for COX-2 than COX-1. Further, prodigiosin was nontoxic to rat islet (RIN-5F) cells in an assay with 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenylteterazolium bromide) in vitro, and its morphological characteristics of cell shape, clumping, chromatin, and nuclear morphology were normal when viewed under bright light microscopy. Finally, prodigiosin was tested for anti-inflammatory properties against lipopolysaccharide-induced RIN-5F cells. The tests revealed that prodigiosin protected against elution of inflammatory markers like NO, interleukin-6 (IL6), and IL8 in a dose-dependent manner. Graphical Abstract: ga1 Highlights: Isolation and characterization of prodigiosin from several substrates. Prodigiosin exhibited good microbial activity against select bacteria and fungi. In silico docking of prodigiosin with anti-inflammatory genes was studied. Prodigiosin was demonstrated to be nontoxic to rat islet (RIN-5F) cells. Prodigiosin showed good anti-inflammatory activity against inflammation. This research can be a novel platform for industrial and biomedical applications.